Acquired progressive lymphangioma: Case report with partial response to imiquimod 5% cream. Issue 6 (21st September 2017) - Salman, Andac; Sarac, Gonca; Can Kuru, Burce; Cinel, Leyla; Yucelten, Ayse Deniz; Ergun, Tulin
Abstract: Acquired progressive lymphangioma (APL), or benign lymphangioendothelioma, is an unusual entity derived from vascular structures. Clinically and histopathologically it may resemble Kaposi's sarcoma and well‐differentiated angiosarcoma, causing a diagnostic problem. We report an individual with APL initially diagnosed with Kaposi's sarcoma who underwent unnecessary laboratory testing. Imiquimod 5% cream stopped the progression of the lesion. Awareness of this rare entity may prevent patients from undergoing excessive testing. Imiquimod may be used as a safe, effective treatment option.